2017 IEEE Biomedical Circuits and Systems Conference (BioCAS) 2017
DOI: 10.1109/biocas.2017.8325122
|View full text |Cite
|
Sign up to set email alerts
|

An objective assessment to investigate the impact of turning angle on freezing of gait in Parkinson's disease

Abstract: Freezing of gait (FoG) is often described in subjects with Parkinson's disease (PD) as a sudden inability to continue the forward walking progression. FoG occurs most often during turning, especially at sharp angles. Here, we investigated 180 and 360 degrees turns in two groups: PD subjects reporting FoG (FoG+), and PD subjects without FoG (FoG-). Forty-three subjects (25 FoG+, 18 FoG-) wore an inertial sensor on their back while walking back and forth continuously for 2 min (reversing direction with a 180° tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The papers considered to compose this study are listed in Table 1. [14] X BECK (2015) [15] X X HANDOJOSENO (2015) [20] X X KILLANE (2015) [21] X X WAECHTER (2015) [22] X X CANDO (2016) [23] X X X X TARD (2016) [24] X BERTOLI (2017) [1] X X MURALIDHARAN (2017) [25] X…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The papers considered to compose this study are listed in Table 1. [14] X BECK (2015) [15] X X HANDOJOSENO (2015) [20] X X KILLANE (2015) [21] X X WAECHTER (2015) [22] X X CANDO (2016) [23] X X X X TARD (2016) [24] X BERTOLI (2017) [1] X X MURALIDHARAN (2017) [25] X…”
Section: Literature Reviewmentioning
confidence: 99%
“…The following combinations of terms were used to maximize the scope and type of material referred in the search: FOG is usually triggered by postural transitions [1], the triggers considered to be a possible manner of causing FOG, according to the literature review, are to sit and stand up from a chair, walk through a doorway, reach a destination, turn 180° and 360°, and carry out a dual task. The triggers considered in each study included in the literature review are shown in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations